India : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper presents an analysis of trends in growth and investment in India in the 1990s, with a focus on the slowdown in growth during the second half of the 1990s. The paper discusses the fiscal situation, outlining the key reasons for the deterioration in fiscal balances, how the fiscal situation compares with other developing countries, and the key lessons from countries that managed successful fiscal consolidation. The paper also contains an assessment of India's opening to global trade and factors that may be affecting India's export performance.